Matter Nature “Matters” Ultimately: A Material Ecological Reflection on Psalm 65: Festschrift for Willie van Heerden - Viviers, Hendrik (Journal for Semitics, 2021)
Modern insights in philosophy, anthropology, psychology, communication studies, religion studies and art history (to name but a few), exemplify the so-called material turn in the study of religion, of how matter “matters,” even ultimately. Contributions in the recently founded journal, Material Religion: The Journal of Objects, Art and Belief, highlight these insights. Humans animate material “things” (e.g., land, nature, temples, shrines) with meaning, and they in turn become “agents” to mediate the meaningful world they stand for. Humans and matter become co-constitutive in this dynamic. Our senses and sensibilities play a crucial role in this “world making” endeavour, when interacting with the material world around us. Ecological hermeneutics concurs, regarding Earth as a “subject” in her own right. This study found that an ancient poem, Psalm 65, resonates with these modern insights. The psalm expresses a skilful interconnectedness in its composition, but moreover, it interconnects temple(-goers; vv. 2–5), the orderly cosmos (vv. 6–9) and the fertile land (vv. 10–14) in unified and thankful song towards their creator and sustainer. The sensual experience of the “goodness” in the temple in Zion, the awe-inspiring cosmos, and the “goodness” of the fertile land, realises this “world of bliss.”
paid
Keywords: Psalm 65; ecological hermeneutics; materiality; matter; senses; sensibility